2013
DOI: 10.4103/0972-124x.118313
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of xanthan based chlorhexidine gel as an adjunct to scaling and root planing in treatment of the chronic periodontitis

Abstract: Aim:The aim of this study was to evaluate the clinical effectiveness of locally delivered xanthan-based Chlosite® gel as an adjunctive therapy to scaling and root planing in treatment of chronic periodontitis.Materials and Methods:In a randomized controlled clinical study, 30 patients were selected. Pocket depth between 5 and 7 mm was selected and each patient had two sites on the same side of the mouth. A total of 30 control sites were scaled and root planed and 30 test sites were scaled and root planed and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 13 publications
1
30
0
Order By: Relevance
“…A significant improvement in PPD and/or CAL was reported in a number of studies using XAN-CHX gel 26,27,29,[31][32][33][34] . Whereas, several studies showed no additional benefit in clinical outcomes with the adjunctive use of CHX gel [8][9][10]25,28,30 . In addition, all three studies using CHX gels that did not contain Xanthan gum reported no clinical benefits in the test group [8][9][10] .…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A significant improvement in PPD and/or CAL was reported in a number of studies using XAN-CHX gel 26,27,29,[31][32][33][34] . Whereas, several studies showed no additional benefit in clinical outcomes with the adjunctive use of CHX gel [8][9][10]25,28,30 . In addition, all three studies using CHX gels that did not contain Xanthan gum reported no clinical benefits in the test group [8][9][10] .…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…Seventeen articles met the criteria and were included for qualitative analysis. Thirteen studies reported subgingival application of CHX gel adjunct to SRP at selected sites with a moderate to deep probing depth (at least 4mm in all studies) [8][9][10][25][26][27][28][29][30][31][32][33][34] . Nine studies were split-mouth RCTs 8,10,[26][27][28][31][32][33][34] , four were parallel RCTs 9,25,29,30 and three studies used a placebo in the control 10,30,32 .…”
Section: Description Of the Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Several papers have described information on the noteworthy properties of different excipients which affect on drug absorption and permeability thru intestinal efflux pump. Such as, a previous study reported that tween 80 can shrink the fraction of serosal-mucosal transport to mucosal-serosal transport for Rho-123 through rat jejunal membrane in vitro and caco-2 cell monolayer evocative of p-gp inhibition [13]. Into the bargain, the in vitro amount of absorption for digoxin through a rat gut sac (a p-gp substrate) revealed an intense growth in amounts after treating with 0.5% (w/v) tween 80 and tween 20 [14].…”
mentioning
confidence: 99%